Physiological Responses of the Modified Shuttle Test in Adults With Cystic Fibrosis. Issue 4 (July 2016) - Vallier, Jean-Marc; Rouissi, Mehdi; Mely, Laurent; Gruet, Mathieu
Abstract : PURPOSE: The modified shuttle test (MST) is increasingly used in clinical practice to assess functional capacity in patients with cystic fibrosis (CF). The purpose of this study was to evaluate the physiological responses of the MST in adults with CF as compared with the gold standard cardiopulmonary exercise test (CPET). METHODS: Participants performed an MST and a CPET on a cycle ergometer in random order. Oxygen (O2 ) uptake ( O2 ), carbon dioxide (CO2 ) retention (end-tidal PCO2 ; PETCO2 ), minute ventilation, heart rate, and peripheral O2 saturation (SpO2 ) were continuously monitored. Whole blood lactate, dyspnea, and leg discomfort were recorded immediately after both exercises. RESULTS: Twenty patients with CF (aged 33 ± 8 years; forced expiratory volume in 1 second = 48% ± 17%) completed both tests. Peak values for O2 (27 ± 7 vs 24 ± 6 mL/kg/min), heart rate (169 ± 19 vs 163 ± 16 bpm), end PETCO2 (42 ± 7 vs 39 ± 8 mm Hg), and O2 desaturation (end SpO2, 86% ± 7% vs 90% ± 6%) were significantly higher during the MST than during the CPET (all P s < .05). Leg discomfort and whole blood lactate were significantly higher after the CPET (both P s < .05). Thirty-five percent and 40% of patients showed significant O2 desaturation and CO2 retention, respectively, during the MST, which was not detected during the CPET. A strong relationship was found between MST peak O2 and body weight walking distance product ( r = 0.90; P < .01). CONCLUSIONS: The MST may provide a strong indicator of exercise tolerance in adults with CF as indicated by high peak O2 values. In clinical practice, body weight walking distance should be considered as the primary outcome. This test is also better than cycle ergometry CPET for detecting O2 desaturation and CO2 retention, further emphasizing its clinical interest. Abstract : The modified shuttle test (MST) is among the most popular exercise tests to evaluate physical fitness in cystic fibrosis. We demonstrated that the MST elicited a higher cardiorespiratory and metabolic demand than a standard incremental cycling test and was better at detecting O2 desaturation and CO2 retention, emphasizing its clinical value in this population.